1989
DOI: 10.1002/1097-4679(198909)45:5<736::aid-jclp2270450508>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

The military nurse experience in Vietnam: Stress and impact

Abstract: Demographic, health, and psychosocial data from two studies are presented on military nurses assigned to Vietnam. Army nurse subjects in the first study were grouped for comparison on three major variables: assignment to Vietnam before versus after the 1968 TET Offensive, type of nursing duties performed, and years of experience as a registered nurse (RN) prior to assignment in Vietnam. The second study compared another group of Army nurses with a group of Air Force and Navy nurses also assigned to Vietnam. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 4 publications
(9 reference statements)
1
27
0
Order By: Relevance
“…13 In the case of females, the traumatic event could also imply being the target of sexual harassment or sexual assault by their male colleagues. 80 Rape, regardless of gender, has been consistently found to be one of the most pathogenic traumas. 81 For example, Kilpatrick et al found that crimes involving a rape, physical injuries, and threat to the victim's life increase the likelihood of the victim developing PTSD by 8.5 times compared to crimes in which these three factors are not present.…”
Section: Step 2 Objective Characteristics Associated With Traumatic mentioning
confidence: 99%
“…13 In the case of females, the traumatic event could also imply being the target of sexual harassment or sexual assault by their male colleagues. 80 Rape, regardless of gender, has been consistently found to be one of the most pathogenic traumas. 81 For example, Kilpatrick et al found that crimes involving a rape, physical injuries, and threat to the victim's life increase the likelihood of the victim developing PTSD by 8.5 times compared to crimes in which these three factors are not present.…”
Section: Step 2 Objective Characteristics Associated With Traumatic mentioning
confidence: 99%
“…5,6 These two factors, coupled with other challenges, could have a negative impact on their mental and physical health. Many return to nursing positions where they care for those injured in the war or where they can't practice with the same level of autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Baker et al. (1989) investigated stressful war experiences in 20 Army nurses in regard to hospital duties, prior clinical experience, period of war service, and PTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%